Analisis Spasial Pembangunan Ekonomi Inklusif di Indonesia Tahun 2019, 2020 dan 2021 - Prasetya, Kadek Aris; Saskara, IdaAyu Nyoman; Purwanti, Putu Ayu Paramitha (Jurnal Ekonomi Kuantitatif Terapan, 2025)
Economic development is not only seen from the quantity of growth but also the quality of development. Inclusive economic development is an indicator that can see the quality of development. This research was conducted in all provinces in Indonesia by looking at the spatial inclusive economic development index in 2019, 2020 and 2021. The method of analysis in this study is descriptive analysis that describes the distribution of the inclusive economic development index in all provinces in Indonesia and inferential analysis shown by spatial regression models with spatial effects of the inclusive economic development index. The results showed that the distribution of the inclusive growth index in Indonesia has a spatial effect in 2019, 2020 and 2022. The clustering of high growth index is in Java Island while the low one is in eastern Indonesia. The spatial regression model shows that the inclusive economic development index has a significant spatial effect in 2019, 2020 and 2021. The variables life expectancy, average years of schooling, gross fixed capital formation and open unemployment rate have a significant influence on inclusive economic development in 2019. In 2020 and 2021 the variables average years of schooling and gross fixed capital formation have a positive influence and significant to the inclusive development index. Furthermore, it is necessary to collaborate between local governments in an effort to increase the inclusive growth index given the spatial influence. This is one of the efforts so that economic development can be enjoyed inclusively by all residents in Indonesia.